Seeking intimacy: queer agency, normativity, and emergent identities. Issue 5 (3rd September 2019) - Elund, Jude
ABSTRACT: This paper provides a small snapshot of some of the issues regarding LGBTIQ+ experiences and identities. Of particular importance are the political and personal agencies of personhood and expression – how do individuals perform and experience gender and sexuality outside both heteronormativity and homonormativity? This paper analyses fluidity across geographies and mobilities, with a specific emphasis on age, categorization and identity expression. It also looks at sexual expression in individuals outside of dominant Western culture, as well as post-modern expressions of queerness and social media representations. Most importantly, the paper focuses on homonormativity, non-normativity, and divergent ways of being, interrogating the same-sex marriage debates and legislation in Australia.